Aqueous photodecomposition of the emerging brominated flame retardant tetrabromobisphenol S (TBBPS). (15th February 2021) - Xu, Haiyan; Li, Yueyue; Lu, Jiaxin; Lu, Junhe; Zhou, Lei; Chovelon, Jean-Marc; Ji, Yuefei
Abstract: As an emerging brominated flame retardant (BFR), tetrabromobisphenol S (TBBPS) has been frequently detected in the environmental media and organisms. Knowledges on the transformation and fate of TBBPS in both environment and engineering systems are essential to its ecological risk assessment. Herein, we reported the photochemical decomposition of TBBPS in aqueous solution upon 254 nm ultraviolet irradiation (UV254 ). Results show that TBBPS was highly photoreactive, most likely due to the presence of four ortho- bromine substituents. The molar absorption coefficient and quantum yield of TBBPS were found to be pH-dependent, with the monoanionic form being most photoreactive. A series of photoproducts were identified by solid phase extraction (SPE) combined with liquid chromatography-electrospray ionization-triple quadrupole mass spectrometry (LC-ESI(+)-MS/MS. The photolysis of TBBPS likely proceeded through photonucleophilic substitution, photoreductive debromination, and β -scission reactions. A ketocarbene, possibly derived from the lower lying excited triplet state, was proposed to be involved in the photolysis of TBBPS. Ion chromatography analysis revealed that debromination occurred quickly, and the yield of bromide (Br − ) approached 100% after 90 min irradiation. The presence of SRNOM and MRNOM inhibited the photodegradation rate of TBBPS, which is likely due to the light-screening and physical quenching effects of natural organic matter (NOM). Our results reveal that photolysis is an important process for the attenuation of TBBPS in aquatic system; however, naturally occurring species such as NOM can appreciably retard the decay of TBBPS. Graphical abstract: Image 1 Highlights: TBBPS undergoes photodecomposition upon UV254 irradiation. Monoanionic form is most photoreactive. Photolysis induces debromination and β -scission. Debromination occurs quickly during photolysis. NOMs exhibit inhibitory effects on TBBPS photolysis.